Obsmrtne izkušnje - Klemenc-Ketiš, Zalika (Medicinski razgledi, 2009)
Near-death experiences are experiences of deep feelings of out-of-body experiences and of entering other dimensions outside the usual borders of timeand space. They mostly occur when a person is facing a life-threatening situation, is ne ar death or is even clinically dead. One of the definitions of near-death experiences portrays them as indescribable events that may include feelings of peace, joy and out-of-body existence, moving through a dark tunnel, meeting with deceased or spiritual persons, a retrospective review of one's own life, coming to a point of no return, returning to one's own physical body and profound changes in values and beliefs. According to theinternational classification of diseases, they are classified as religious or spiritual disorders. Many theories (physiological, psychological and trascendental) and combined models have attempted to explain their existence, but so far none of them have provided an acceptable explanation. Near-death experiences affect both the physical and psychological recovery of such patients and also the relationship between the patients and their spouses, families and relatives. Characteristically, patients keep them confidential. Although near-death experiences are mostly positive and as such even protect patients from developing a posttraumatic stress disorder, such patients rarelyseek medical help due to fear of being ridiculed by society in the case of psychological problems. It is nevertheless important for physicians to be aware of their existence and to tre at such patients properly.
Keywords: Death; Smrt; umiranje; Physiopathology; obsmrtne izkušnje; Psychology; psihologija